2001
DOI: 10.1143/jjap.40.l343
|View full text |Cite
|
Sign up to set email alerts
|

Low Temperature Deposition of Pb(Zr,Ti)O3 Film by Source Gas Pulse-Introduced Metalorganic Chemical Vapor Deposition

Abstract: We prepared Pb(Zr,Ti)O 3 [PZT] thin films on (111)Pt/Ti/SiO 2 /Si substrates at 395 to 580 • C by metalorganic chemical vapor deposition (MOCVD). PZT thin films with Zr/(Zr + Ti) = 0.62 prepared by conventional continuous source gas introduction (continuous-MOCVD) and pulse introduction (pulse-MOCVD) were compared. Film with higher crystallinity and smoother surfaces were obtained by pulse-MOCVD compared with continuous-MOCVD. Moreover, the leakage current density of the film decreased and ferroelectricity in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…We used pulsed-MOCVD, in which a mixture of source gases was introduced for 10 seconds at 5 seconds intervals, while oxygen gas was continuously introduced into the reaction chamber. Details of pulsed-MOCVD were reported elsewhere [11][12][13].…”
Section: Methodsmentioning
confidence: 99%
“…We used pulsed-MOCVD, in which a mixture of source gases was introduced for 10 seconds at 5 seconds intervals, while oxygen gas was continuously introduced into the reaction chamber. Details of pulsed-MOCVD were reported elsewhere [11][12][13].…”
Section: Methodsmentioning
confidence: 99%
“…Our group developed a MOCVD process that introduced the source gas mixture into the reactor in pulses (pulsed-MOCVD) for the preparation of PZT films. 10 This method has already proved useful not only in lowering deposition temperature 11,12 but also in depositing films with lower leakage current together with good surface flatness. 10 A previous study found an Ir layer to be an effective bottom electrode to prevent the diffusion of Pb into the bottom electrode and to decrease the leakage current in PZT films, compared to the electrical properties of epitaxial PZT films deposited on ͑100͒Ir/ / ͑100͒MgO and ͑100͒SrRuO 3 / /͑100͒SrTiO 3 substrates.…”
mentioning
confidence: 99%
“…Pulsed growth, with short growth periods interspersed with purge periods, also improves the crystallinity at lower substrate temperatures. This effect has been demonstrated by Funakubo's group; [4][5][6] they attribute the improved crystallinity to the ability of excess PbO (which can serve as a mineralizer and help crystallize PZT) to volatilize and leave the film during the purge periods. We have verified that such pulsed growth can lower the temperature necessary to achieve crystalline films, which can in turn provide material with the desired pyroelectric properties without exceeding the required thermal budget.…”
Section: Pzt Hysteresismentioning
confidence: 87%